Answer:
6.32
Step-by-step explanation:
To find the side length on a right angled triangle we follow The Pythagorean Theorem:
![{a}^{2} + {b}^{2} = {c}^{2}](https://tex.z-dn.net/?f=%20%7Ba%7D%5E%7B2%7D%20%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%20%3D%20%20%7Bc%7D%5E%7B2%7D)
c being the hypothesis (longest side: the hypotenuse is always opposite the right angle)
so..
![{6}^{2} + {2}^{2} = {x}^{2} \\ 36 + 4 = {x}^{2} \\ 40 = {x}^{2} \\ \sqrt{40} = \sqrt{ {x}^{2} } \\](https://tex.z-dn.net/?f=%20%7B6%7D%5E%7B2%7D%20%20%2B%20%20%20%7B2%7D%5E%7B2%7D%20%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20%5C%5C%2036%20%2B%204%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20%5C%5C%2040%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%5C%5C%20%20%5Csqrt%7B40%7D%20%20%20%3D%20%20%5Csqrt%7B%20%7Bx%7D%5E%7B2%7D%20%7D%20%5C%5C%20%20)
![6.32 = x](https://tex.z-dn.net/?f=6.32%20%3D%20x)
d because you take the denominator of the fraction and you put it infront of the square root then you take the numerator and multiply it by the number at hand in this case 7
B. (−3, 2)
I think
so plz have a good rest of ur day
Answer: 56
Step-by-step explanation:
Subtract 43 from both sides
-6p=-30
Divide both sides by -6
p=5
Final answer: p=5